2021
DOI: 10.3389/fphar.2021.714628
|View full text |Cite
|
Sign up to set email alerts
|

Network Pharmacology–Based Identification of Key Mechanisms of Xihuang Pill in the Treatment of Triple-Negative Breast Cancer Stem Cells

Abstract: Xihuang pill, an approved Chinese medicine formula (state medical permit number. Z11020073), is a commonly used adjuvant drug for cancer patients in China. Xihuang pill has a satisfactory effect in treating breast cancer in clinics, especially triple-negative breast cancer (TNBC), which is the most aggressive type of breast cancer, and finite effective therapies. However, the mechanism of Xihuang pill in treating TNBC remains unclear. The present study aims to explore the pharmacological mechanism of Xihuang p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…Using the DAVID database, the GO functional and KEGG pathway enrichment analyses were further performed on potential anti-COVID-19 prime targets by keeping the species threshold of “Homo sapiens” ( 49 , 50 ). There are three categories of GO terms: cellular component (CC), biological process (BP), and molecular function (MF).…”
Section: Methodsmentioning
confidence: 99%
“…Using the DAVID database, the GO functional and KEGG pathway enrichment analyses were further performed on potential anti-COVID-19 prime targets by keeping the species threshold of “Homo sapiens” ( 49 , 50 ). There are three categories of GO terms: cellular component (CC), biological process (BP), and molecular function (MF).…”
Section: Methodsmentioning
confidence: 99%
“…Gene ontology (GO) functional enrichment analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis were carried out using the DAVID database for annotation, visualization, and integrated discovery (Version 6.8; https://david.ncifcrf.gov/ , accessed on December 16, 2021) [ 35 – 37 ]. The GO terms were categorized into three types: cellular component (CC), biological process (BP), and molecular function (MF).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Hermawan et al found that naringenin inhibited BCSC mammosphere formation, potentially through the modulation of p53 and ERα mRNA [ 82 ]. Naringenin was also identified as the active compound in the Xihuang pill, a traditional medicine used to treat breast cancer in China [ 156 ]. In vitro, both the Xihuang pill and naringenin inhibited mammosphere formation in triple negative breast cancer cell lines by upregulating NR3C2 expression [ 156 ].…”
Section: Phytoestrogens Targeting Bcscs and Their Mechanisms Of Actionmentioning
confidence: 99%